2020
DOI: 10.1177/0739986320937435
|View full text |Cite
|
Sign up to set email alerts
|

Family and Family-Like Relations for Transnational Migrants: Ideals of Care Informed by Kin, Non-Family, and Religion

Abstract: Studies of transnational family formation and care relationships suggest that, while family forms and care values are idealized, they are also negotiated, enacted, and fluid constructs. Strategies of resilience and mechanisms of flexible care achieved by transnational families are fine-tuned under multiple influences. Among these influences are well-known sources such as social networks, as well as less well-understood sources such as religious teachings. We report findings of a 4-month, ethnographic study amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…In this sense, a study carried out in the USA pointed out that it is this hope that motivates immigrants to experience family relationships, even at a distance 18 . Also in the US, an ethnographic study that analyzed resilience strategies and mechanisms to keep transnational families functioning showed that immigrants provide care to their families who migrated, but also need to provide support to those who stayed in the country of origin, continuing their roles even in the face of new contexts [28][29] . Thus, while physical distance is present, in order to maintain the family bond, the immigrants in this study referred to the willingness and efforts undertaken to financially help those who stayed in their countries of origin.…”
Section: /14mentioning
confidence: 99%
“…In this sense, a study carried out in the USA pointed out that it is this hope that motivates immigrants to experience family relationships, even at a distance 18 . Also in the US, an ethnographic study that analyzed resilience strategies and mechanisms to keep transnational families functioning showed that immigrants provide care to their families who migrated, but also need to provide support to those who stayed in the country of origin, continuing their roles even in the face of new contexts [28][29] . Thus, while physical distance is present, in order to maintain the family bond, the immigrants in this study referred to the willingness and efforts undertaken to financially help those who stayed in their countries of origin.…”
Section: /14mentioning
confidence: 99%
“…Neste sentido, estudo realizado nos EUA apontou que é esta esperança que motiva os imigrantes a vivenciarem o relacionamento familiar, mesmo sendo à distância 18 . Também nos EUA, estudo etnográfico que analisou as estratégias de resiliência e os mecanismos para manter o funcionamento de famílias transnacionais, mostrou que os imigrantes prestam cuidados aos seus familiares que migraram, mas também necessitam prestar apoio àqueles que ficaram no país de origem, dando continuidade em seus papéis mesmo diante de novos contextos [28][29] . Desse modo, enquanto a distância física se faz presente, para manter o vínculo familiar, os imigrantes desse estudo fizeram referência à disposição e aos esforços empreendidos para ajudar financeiramente aqueles que ficaram em seus países de origem.…”
Section: /14unclassified
“…Research on familism and family‐like care suggest that narrowly construed ideas about family influence (Smith‐Morris et al. 2012; Thomas and Smith‐Morris 2020) can be a stigmatizing and acculturative force.…”
Section: How White Settler Idioms Blame Families For Multigenerational Inequitymentioning
confidence: 99%